Genotyping of CCR5 Gene, CCR2b and SDF1 Variants Related to HIV-1 Infection in Gabonese Subjects - Mombo, Landry Erik; Bisseye, Cyrille; Mickala, Patrick; Ossari, Simon; Makuwa, Maria (Intervirology, 2015)
Objective: Given the magnitude of the HIV epidemic infection, many viral and human factors were analyzed, and the most decisive was the variant CCR5-Δ32. The presence of a low HIV prevalence (1.8%) in Gabon in the 1990s, compared to neighboring countries, represents a paradox that led us to search for viral and human genetic variants in this country. In this study, only variants of coreceptors and chemokines were investigated. Methods: Variants of the coding region of the CCR5 gene were analyzed by denaturing gradient gel electrophoresis, and then variants of SDF1 and CCR2b were determined by polymerase chain reaction-restriction fragment length polymorphism. Results: Four rare variants of the CCR5 coreceptor were found, while CCR5-Δ32 and CCR5m303 variants were not found. No association with CCR2b-V64I (17%) and SDF1-3′A (2%) variants was determined in relation to HIV-1 infection in Gabonese patients. Conclusion: The paradox of HIV seroprevalence in Gabon, which ended in the 2000s, was not caused by human genetic variants but rather by environmental factors.